(untitled) (INNOVATIVE ECONOMY, 2025)
Strotsen A.I., Mazuryk V.R. STRATEGIC ACCOUNTING OF DESIGN AND PREPRESS COSTS IN ENSURING THE EFFECTIVENESS OF MANAGEMENT DECISIONS Purpose. The aim of the article is to substantiate the theoretical and methodological foundations of strategic accounting of design and prepress costs as an integral component of the enterprise management system and as a basis for forming an information framework for effective managerial decision-making. Methodology of research. The study employed the methods of theoretical generalization and grouping to define the essence of strategic accounting; analysis and synthesis to adapt existing costing methods to the needs of creative processes; a systemic approach to model the formation of accounting information; the comparative method to contrast traditional and strategic approaches; and logical generalization of results to formulate conclusions and practical recommendations. Findings. It has been proved that design and prepress costs have a strategic nature, since they determine not only the cost level but also the market attractiveness of products. It was established that the use of strategic costing methods ensures the separation of creative costs from general overhead, allows assessing their real contribution to value formation, and enables cost management in line with market expectations and the product lifecycle. An approach to the use of strategic cost maps was developed, integrating design and prepress into the system of key strategic indicators of the enterprise. Originality. Scientific novelty lies in refining the theoretical and methodological foundations of strategic accounting of creative costs, in particular by identifying design and prepress as strategic factors in creating added value. A concept is proposed for integrating strategic costing methods into the management system of publishing enterprises, which makes it possible to account for the impact of creative costs on competitiveness and product positioning in the market. The novelty is also reflected in the suggested approach to the use of strategic cost maps, which establish a link between creative expenses and key performance indicators. Practical value. The results can be applied by publishing enterprises to optimize creative expenses, plan innovative projects, and determine the feasibility of investments in design and prepress. The proposed tools make it possible to more accurately determine product cost, calculate break-even points for innovative solutions, substantiate price premiums, and define optimal print runs. In the long-term perspective, this will contribute to increasing the effectiveness of managerial decisions, minimizing risks, and enhancing the competitiveness of publishing enterprises. Further research should focus on deepening the methodology of strategic accounting of creative costs in a digital environment, developing risk-oriented approaches to their management, as well as integrating strategic accounting with marketing analytics and quality management systems. Key words: strategic accounting, management accounting, design costs, prepress costs, costing, publishing activity, strategic management decisions.